2007
DOI: 10.1111/j.1440-1746.2006.04819.x
|View full text |Cite|
|
Sign up to set email alerts
|

PPAR agonists treatment is effective in a nonalcoholic fatty liver disease animal model by modulating fatty‐acid metabolic enzymes

Abstract: Background and Aims: In a previous study, the authors found that reduced expression of peroxisome proliferator-activated receptor (PPAR)-a might play an important role in developing nonalcoholic fatty liver disease (NAFLD). The aim of this study was to analyze the effects of PPAR-a and -g agonists on NAFLD and verify the mechanisms underlying the PPAR-a and -g agonist-induced improvements by evaluating the hepatic gene expression profile involved in fatty-acid metabolism, using the Otsuka-Long Evans-Tokushima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 42 publications
(85 reference statements)
7
82
0
4
Order By: Relevance
“…It was suggested that PPARα activation by fenofibrate enhances hepatic FA turnover. Namely, it increased mRNA expression of FA β-oxidation enzymes in obese rats with T2DM [76] . These include FA transport protein, FA binding protein, carnitine palmitoyltransferase II, as well as medium-and longchain acyl-CoA dehydrogenase and acyl-CoA oxidase [76,77] .…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that PPARα activation by fenofibrate enhances hepatic FA turnover. Namely, it increased mRNA expression of FA β-oxidation enzymes in obese rats with T2DM [76] . These include FA transport protein, FA binding protein, carnitine palmitoyltransferase II, as well as medium-and longchain acyl-CoA dehydrogenase and acyl-CoA oxidase [76,77] .…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…Namely, it increased mRNA expression of FA β-oxidation enzymes in obese rats with T2DM [76] . These include FA transport protein, FA binding protein, carnitine palmitoyltransferase II, as well as medium-and longchain acyl-CoA dehydrogenase and acyl-CoA oxidase [76,77] . A high-fat diet-associated increase in the liver inflammatory gene expression may be ameliorated by fenofibrate [74] .…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…So, as a TNF-a blocker, pentoxifylline improves both steatosis and inflammation in patients with NAFLD and NASH (64)(65)(66). Antioxidants showed modest improvement in steatosis and lobular inflammation, with no effect on body weight, waist circumference, LDL-cholesterol, and fibrosis (48,67).…”
Section: Therapy Of Nafld and Nashmentioning
confidence: 99%
“…Fenofibrate, a PPARα agonist, can specifically bind to PPARα and activate expression of numerous genes participating in fatty acid oxidation, control of triglycerides and cholesterol metabolism (9,10). Fenofibrate, therefore, was very effective to the nonalcoholic fatty liver diseases by modulating lipid metabolic enzymes such as fatty acid transport protein, fatty acid binding protein, long chain acyl-CoA dehydrogenase and acyl-CoA oxidase (11). The abdominal and skeletal adiposity in the diabetic rats was greatly improved by treatment with fenofibrate (4).…”
Section: Introductionmentioning
confidence: 99%